Effect of increasing cow urine patch area on nitrogen losses from grazed pastures : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Soil Science at Massey University, Palmerston North, New Zealand - Hedges, May Tana (Massey University, 2024)
The expansion and intensification of dairy farming in New Zealand (NZ) over the last few decades has made a major contribution to the country’s greenhouse gas emissions, and to the nitrogen (N) enrichment of its surface and ground waters. The environmental concerns associated with dairy farming have led researchers to investigate potential mitigations to reduce N losses from cow urine patches, which are the main source of N losses. However, there has been little research conducted on the effect of increasing the spread area of urine patches as a mitigation for N losses. The development of a prototype urine spreading device, intended to be worn by cows during summer and autumn, has made such a mitigation possible. The primary aim of this device is to provide a method to reduce nitrate (NO₃⁻) leaching, by directly reducing the N application rate in the urine patch. The impact of increasing the size of the urine patch on N emissions to the atmosphere is also an important consideration. Research was required to quantify the effects of increasing urine spread on N losses from urine patches. This research quantified the effect of increasing the urine patch spread area on ammonia (NH₃) and nitrous oxide (N₂O) emissions, and on NO₃⁻ leaching losses. The first field experiment was conducted in early autumn on Dairy Farm 1, Massey University, near Palmerston North, New Zealand. The soil at the site is a Manawatu silt loam. Three urine application depth treatments of 10 mm, 5 mm and 2.5 mm were applied to an area (0.018 m²) inside a series of 20 chambers (5 replicates). These treatments represented the depths that would result from applying 2.5 L of urine to three different patch areas: 0.25 m² (i.e. typical patch size), 0.5 m² and 1 m², respectively. A control treatment with no urine applied was also included. The concentration of total N in applied urine was 4.53 g N L⁻¹. Ammonia measurements were conducted over a period of 20 days using the Dynamic Chamber method. Soil samples were also collected periodically from adjacent treatment plots to measure mineral-N (nitrate and ammonium), soil moisture and pH. The results showed that increasing the urine patch area from 0.25 to 1 m² has increased total NH₃ emissions from 25 to 36% of the total urine-N applied and, consequently the emission factor also increased. This NH₃ increase also increases indirect N₂O emissions, which can have an influence on annual emissions. However, the loss of NH₃ from the urine patch also reduces the amount of urinary N that is available for subsequent direct N₂O emissions and NO₃⁻ leaching. The second and third field experiments were carried out on Dairy Farm 4, Massey University. The soil type at both sites is the Tokomaru silt loam soil. One of the field experiments involved urine application in early-autumn and the other in early-winter. Urine collected from lactating dairy cows was applied to small, mowed plots at application depths of 10 mm (applied to 0.25 m²), 5 mm (applied to 0.5 m²) and 2.5 mm (applied to 0.5 m² and results were extrapolated to a notional patch area of 1 m²). A control treatment with no urine applied was also included. All treatments were replicated five times. Gas sampling was conducted in the field using the static chamber method (chamber area of 0.50 m²). The results of these studies showed that increasing the size of the urine patches from 0.25 to 1 m² with the same volume of urine-N in early-winter did not significantly increase N₂O emissions and emission factors (EF₃). Although increasing the urine patch area increased N₂O emission by 39%, this difference was not large enough to be statistically significant (P>0.05). However, for the first 14 days of total N₂O emissions, the 1 m² urine patch treatment was statistically different (P<0.05) from the 0.25 m² urine patch treatment. In contrast, increasing the size of the urine patches from 0.25 to 1 m² in early-autumn decreased N₂O emissions and EF₃ by 56% (P<0.05). The different effect of increasing the urine patch area in these two different seasons, is likely to be attributed to the differences in soil moisture conditions at the time of urine application and the weeks that followed. To determine the overall effect on N₂O emissions, the reduction in N₂O emissions in autumn was compared with the increase in NH₃ emissions at this time using the N₂O inventory emission value of 0.1 for indirect emissions. These indirect N₂O emissions was estimated to be about 3.6 times higher than the reduction in direct N₂O emissions. Therefore, the use of a urine spreading device to increase the spread area of cow urine in autumn is expected to result in greater overall accumulation of N₂O in the atmosphere. The fourth experiment was conducted on Dairy Farm 4, Massey University. The experimental paddock consisted of twelve pasture plots measuring 800 m² per plot, with separate mole and pipe drainage systems. There were two treatments and six replicates of each treatment. The treatments were cows wearing urine-spreading devices (‘Device’ treatment) and without the device (‘Control’ treatment). The devices were used on four grazing events over the late summer and autumn period. Drainage water from the plots was monitored and analysed for total N and NO₃⁻-N, and pasture accumulation measurements were also conducted. Overall N leaching losses were low, and the differences in total N and NO₃⁻ leaching between the two treatments were small and not statistically significant (P>0.05). There were also no differences in pasture accumulation over a 9-month period. Further improvements to the device are required to consistently increase the spread area of urine patches and the uniformity of the spread. The improved device should then be evaluated over a number of years to assess its potential to reduce leaching of N and its impact on N gaseous emissions to the atmosphere.
Keywords: urine patch area, urine spreading device, ammonia emissions, nitrous oxide emissions, nitrate leaching, soil nitrate, soil ammonium, soil moisture; 410604 Soil chemistry and soil carbon sequestration (excl. carbon sequestration science); 300307 Environmental studies in animal production